Study on the Train-induced Environmental Vibrations Considering Soil-Structure Interaction. (2017) - Yao, J.B.; Xia, H.; Zhan, N.
Abstract: With the development of national economy and the improvement of people's living standards, the problem of environmental vibrations has been more concerned. The traffic-induced vibrations can propagate through the surrounding soil, inducing secondary vibrations and noises of nearby buildings, which have considerable effect on the safety of structure, the routine life and work of residents living in buildings along traffic-lines. In order to predict the vibration of building induced by train, the model of train-track-soil-interface-building system is established based on the dynamic interaction influence of soil-building foundation in this paper. In the model, the formula of vibration prediction is presented under two contact modes between soil and building foundation, namely, distortion coordination and nonlinear contact. By statistical analysis, the building vibration can be attained considering a lot of influence factors such as train speed, distance between train and building as well as vehicle type.